Brain drain in Algeria and the requirements to limit waste of human competencies - Djebbar, Abdeldjebbar (Journal of Human Sciences, 2020)
Algeria, like all developing countries, has seen a rise in brain drain. Therefore, this is what this study research at as well as determine its negative repercussions as a waste of human competencies, and then the state should adopt youth policies trying to attract it. By activating the mechanisms of empowerment youth in Algeria. Accordingly, the study concluded that the adopting of effective youth policies require research in the determinants of the brain drain, by a development strategy of highly efficient human energies, and the improvement of internal conditions. This enhances the polarizing capabilities of the youthful energies.